Secondary pure red cell aplasia in multiple myeloma treated with lenalidomide. (2018) - Ito, Tomoki; Nakaya, Aya; Fujita, Shinya; Satake, Atsushi; Nakanishi, Takahisa; Azuma, Yoshiko; Tsubokura, Yukie; Konishi, Akiko; Hotta, Masaaki; Yoshimura, Hideaki; Ishii, Kazuyoshi; Nomura, Shosaku
Abstract: Pure red cell aplasia (PRCA) is a rare disorder characterized by marked erythroid hypoplasia with maturation arrest in the bone marrow. Secondary acquired PRCA may be associated with hematologic disorders. A few case reports have described PRCA associated with multiple myeloma (MM). However, the clinical course and mechanism of PRCA associated with MM remain unknown. We herein report two cases of PRCA associated with MM in patients undergoing treatment with lenalidomide.